2016
DOI: 10.1517/13543776.2016.1154540
|View full text |Cite
|
Sign up to set email alerts
|

Protease activated receptor 2 (PAR2) modulators: a patent review (2010–2015)

Abstract: In the last six years, substantial efforts were made towards developing PAR2 modulators, but most lack potency or selectivity or have poor pharmacokinetic profiles. Many PAR2 modulators were assessed by measuring Gαq protein-mediated calcium release in cells. This may be insufficient to fully characterize ligand function, since different ligands signal through PAR2 via multiple signaling pathways. It may be feasible to develop biased ligands as drugs that can selectively modulate one or more specific signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 99 publications
1
30
0
Order By: Relevance
“…PmC-fibers are not itch-“selective” and the neuronal encoding that allow these afferents to act as both pruriceptive and nociceptive fibers under different conditions is a matter of ongoing contention [38, 39]. Currently, no treatments directly targeting itch and pain relevant transduction receptors on PmC-fibers are available (but several are under development [40, 41]).…”
Section: Nociceptive and Pruriceptive Innervation Of The Corneamentioning
confidence: 99%
“…PmC-fibers are not itch-“selective” and the neuronal encoding that allow these afferents to act as both pruriceptive and nociceptive fibers under different conditions is a matter of ongoing contention [38, 39]. Currently, no treatments directly targeting itch and pain relevant transduction receptors on PmC-fibers are available (but several are under development [40, 41]).…”
Section: Nociceptive and Pruriceptive Innervation Of The Corneamentioning
confidence: 99%
“…Cell context-dependent signaling mechanisms that rely on the expression of cofactors, noncanonical cleavage, and their downstream effectors have been described. 6,7 Biased signaling by APC through PAR-1 is responsible for a variety of cyto-protective, neuroprotective, and anti-inflammatory effects and is of considerable therapeutic interest. Canonical cleavage of PAR-1 at Arg41 by thrombin and at a noncanonical site, Arg46, by activated protein C (APC) has been observed.…”
mentioning
confidence: 99%
“…Canonical cleavage of PAR-1 at Arg41 by thrombin and at a noncanonical site, Arg46, by activated protein C (APC) has been observed. 6 In the case of PAR-2, elastase and plasma kallikrein have both been described to cleave outside the canonical 7 Arg36 position that is targeted by trypsin, factor Xa, and tryptase. PAR-1, PAR-3, and PAR-4 mediate platelet activation, whereas PAR-1 and -2 regulate vascular tone, inflammation, thrombosis, atherosclerosis, and cancer.…”
mentioning
confidence: 99%
“…From a clinical perspective, elevated PAR2 expression in biopsy and metastatic tissue could be linked to an increased malignancy grade and subsequently to a decreased overall survival rate . Whereas initial PAR2‐inhibiting compounds were mostly limited in potency or displayed agonistic properties at higher concentrations, recent medicinal chemistry approaches have led to more efficacious small‐molecule PAR2 antagonists . Overall, the distinct role of PAR2 in tumor biology illustrates the need for low‐molecular‐weight PAR2 inhibitors providing the basis for the development of a novel therapeutic strategy in cancer treatment …”
Section: Introductionmentioning
confidence: 99%
“…[6] Whereas initial PAR2-inhibiting compounds were mostly limited in potency or displayed agonistic properties at higherc oncentrations, recent medicinalc hemistry approaches have led to more efficaciouss mall-molecule PAR2 antagonists. [7,8] Overall, the distinct role of PAR2 in tumor biology illustrates the need for lowmolecular-weight PAR2 inhibitors providing the basis for the development of an ovel therapeutic strategy in cancert reatment. [9,10] In the course of our previousw ork, we recently demonstrated that some marine naturalp roducts of the indolactam/teleocidin family exhibit significant effects as PAR2 inhibitors.…”
Section: Introductionmentioning
confidence: 99%